Current and innovative approaches in the treatment of non-muscle invasive bladder cancer - Taskovska, Milena (Radiology and oncology (Ljubljana), 2020)
Background. Bladder cancer is the 7th most common cancer in men. About 75% of all bladder cancer are nonmuscle invasive (NMIBC). The golden standard for definite diagnosis and first-line treatment of NMIBC is transurethral resection of bladder tumour (TURB). Historically, the monopolar current was used first, today bipolar current is preferred by most urologists. Following TURB, depending on the tumour grade, additional intravesical chemo- or/and immunotherapy is indicated, in order to prevent recurrence and need for surgical resection. Development of new technologies, molecular and cell biology, enabled scientists to develop organoids % systems of human cells that are cultivated in the laboratory and have characteristics of the tissue from which they were harvested. In the field of urologic cancers, the organoids are used mainly for studying the course of different diseases, however, in the field of bladder cancer the data are scarce. Conclusions. Different currents - monopolar and bipolar, have different effect on urothelium, that is important for oncological results and pathohistological interpretation. Specimens of bladder cancer can be used for preparation of organoids that are further used for studying carcinogenesis. Bladder organoids are step towards personalised medicine, especially for testing effectiveness of chemo-/immunotherapeutics.
Keywords: rak (medicina); sečni mehur; transuretralna resekcija; zdravljenje